DBR‐free semiconductor disc laser on SiC heatspreader emitting 10.1 W at 1007 nm. Issue 23 (1st November 2017) - Mirkhanov, S.; Quarterman, A.H.; Kahle, H.; Bek, R.; Pecoroni, R.; Smyth, C.J.C.; Vollmer, S.; Swift, S.; Michler, P.; Jetter, M.; Wilcox, K.G.
Abstract : We report a distributed Bragg reflector‐free semiconductor disc laser which emits 10 W continuous wave output power at a wavelength of 1007 nm when pumped with 40 W at 808 nm, focused into a 230 μm diameter spot on the gain chip. By introducing a birefringent filter plate in the laser cavity the wavelength could be tuned from 995 to 1020 nm. The laser consisted of a gain chip located at the beam waist of a linear concentric resonator with an output coupling of 2.15%. The gain chip consists of a 1.574‐μm‐thick resonant periodic gain structure, with ten In0.13 Ga0.87 As quantum wells embedded in strain‐compensating GaAs0.94 P0.06 barrier layers, van der Waals bonded to a silicon carbide intra‐cavity heat spreader.